News Media and Emergency Management Community Interactions Panel - Cole, John; Jarema, Julia; Johnson, Nate; Waters, Skip (My University, 2012)
North Carolina Emergency Management in partnership with East Carolina University's Center for Natural Hazards Research and the Renaissance Computing Institute's Engagement Center at ECU held a Hurricane Workshop on May 23, 2012 at the Murphy Center in Greenville, NC. Over 150 emergency managers, meteorologists, public information officers, emergency responders and university researchers gathered to discuss the lessons learned from Hurricane Irene, improvements to weather forecasting, and discuss challenges faced by emergency and communications professionals. Highlights of the workshop:
Keywords: Hurricanes; Emergency management; NCEM